ANALISIS FAKTOR FAKTOR YANG MEMPENGARUHI EKSPOR MANUFAKTUR KOMODITAS FERONIKEL INDONESIA KE CHINA - Haviz Permana; Sri Ulfa Sentosa (Universitas Negeri Padang, 2026)
This study examines the determinants of Indonesia's ferronickel exports to China during the period 2016Q1-2023Q4, focusing on China's consumer price index (CPI), the international price of ferronickel, China's gross domestic product (GDP), and the Rupiah/US Dollar exchange rate. Quarterly secondary data were obtained from Trade Map and related sources and analyzed using multiple linear regression with the Ordinary Least Squares (OLS) method in EViews, following a log-log specification and standard classical assumption tests. The results show that the international price of ferronickel and China's GDP have a positive and statistically significant effect on export value, while China's CPI and the exchange rate show no significant effect. The model explains about 81.4 percent of the variation in export value (R² = 0.8143) and is jointly significant (F = 29.59; p < 0.01). These findings indicate that Indonesia's ferronickel exports to China are driven mainly by global price dynamics and the strength of Chinese economic growth rather than short-term monetary factors. The study recommends that policymakers strengthen downstream mineral processing policy, diversify export markets, and improve production efficiency to sustain competitiveness amid global price fluctuations.